NR4A1 as a potential therapeutic target in colon adenocarcinoma: a computational analysis of immune infiltration and drug response - Li, Mei; Zhang, Zhongyi; Li, Mingzhou; Chen, Zhe; Tang, Weizhu; Cheng, Xiang (Frontiers in Genetics, 2023)
Background: Colon adenocarcinoma (COAD) is a common malignancy with high morbidity and mortality rates. The immune system plays a crucial role in CRC development and progression, making it a potential therapeutic target. In this study, we analyzed transcriptomic data from CRC patients to investigate immune infiltration and identify potential therapeutic targets.Method and results: we used CIBERSORT to analyze the immune infiltration in COAD samples and found that the high infiltration of M2 macrophages and neutrophils was associated with poor prognosis. Next, we identified NR4A1 as a potential therapeutic target based on its protective effect in two predict models. Using cancer therapeutics response analysis, we found that high expression levels of NR4A1 were sensitive to OSI-930, a tyrosine kinase inhibitor with anti-tumor effects.Conclusions: Our findings suggest that targeting NR4A1 with OSI-930 may be a promising therapeutic strategy for COAD patients with high levels of immune infiltration. However, further studies are needed to investigate the clinical efficacy of this approach.